Microsoft Outlook programming jumpstart for administrators, power users, and developers - Mosher, Sue, 1953- (Amsterdam : Digital Press, 2003)
Microsoft Outlook Programming unleashes the power of Microsoft Outlook, allowing administrators and end users to customize Outlook in the same way that they've used macros and templates to customize other programs like Excel and Word. Experienced developers will find the quick-start information they need to begin integrating Outlook into their applications. Microsoft Exchange administrators will get help automating common tasks such as announcing public folders and importing data to custom forms. Microsoft Outlook is the most widely used email program, and it offers the most programmability. This book introduces key concepts for programming both Outlook forms for storing and exchanging data and Visual Basic for Applications modules that add new features to Outlook. Central to this new edition, which covers both Outlook 2000 and Outlook 2002, is awareness of tighter security in Outlook. Designed to prevent transmission of computer viruses, the security restrictions can also get in the way of legitimate programs, but this book offers workarounds within the reach of novice programmers. It also covers many of the new features of Outlook 2002, such as the integrated Outlook View Control and searching across multiple folders using SQL syntax and the Search object. Building block procedures for the most common Outlook programming tasks Jargon-free language and practical examples to make the material more accessible to new Outlook programmers Coverage of Outlook Email Security Update Coverage of the Office XP Web Services Toolkit.
What you can do with Outlook -- The VBA design environment -- A VBA birthday/anniversary reminder form -- Code basics -- Code grammar 101 -- Working with expressions and functions -- Controlling program flow -- Handling errors and debugging VBA applications -- Handling user input and feedback -- Working with the object models -- Responding to outlook events in VBA -- Working with stores and folders -- Understanding Outlook security -- Working with items and recipients -- Outlook's six basic forms -- Creating your first custom contact form -- Extending form design with fields and controls -- Writing code to respond to outlook form events -- More controls for outlook forms -- Common outlook form and item techniques -- Menus, toolbars, and the outlook bar -- Designing outlook reports -- Exchange server, databases, and XML web services -- Deploying forms and applications.
"Communications"--Cover.
Includes index.
Keywords: Microsoft Outlook; Business -- Computer programs; Electronic books